ANALYSIS OF INDICATORS OF RELIABILITY OF ELECTRICAL NETWORKS - Popescu V. (Problems of the Regional Energetics)
Problems of the optimization reliability in electrical networks of the different class of voltage have probabilistic nature, they discretely change and depend on the number of factors both definite and indefinite and have importance by selection of electric equipment, graph of development of electrical networks and voltage levels. The definition of the major factors, which have determining significance on their value and speed of their change allow to elaborate methods of their optimization and to elaborate effective methods of their growth limitation in electrical networks with the different class of voltage.